Ancient Near Eastern Seals in Birmingham Collections - Lambert, W. G.
Birmingham City Museum, 541΄65-582΄65; Selly Oak Colleges Library, 6-9, 11-15; University of Birmingham, 1-12; private collections; 85 seals: Jemdet Nasr, Early Dynastie I and III, Elamite(?), Old Akkadian, “Post-Akkad”, Third Dynasty of Ur, Old Babylonian, Kassite, Late Assyrian, Late Babylonian, Achaemenid, Peripheral and Doubtful, Sassanian.